Antibiotics resistance phenomenon and virulence ability in bacteria from water environment. Issue 2 (1st October 2017) - Azzam, Mohamed I.; Ezzat, Safaa M.; Othman, Badawi A.; El-Dougdoug, Khaled A.
Abstract: This study aims to determine the impact of five main drains as sources of antibiotics resistant bacteria in River Nile at Rosetta branch, and to generate a baseline data on their virulence ability. Out of 212 bacterial isolates, 39.2% and 60.8% were recovered from drains and Rosetta branch, respectively. Susceptibility of bacteria to different antibiotics showed multiple antibiotics resistances (MAR) for the majority of isolates. Meanwhile, sensitivity was mostly directed to ofloxacin and norfloxacin antibiotics. Calculated MAR index values (>0.25) classified area of study as potentially health risk environment. Testing virulence ability of bacteria from drains showed positive results (65%). Contrastively, virulent strains in Rosetta branch were mostly lacking in this study. Concluding remarks justify the strong correlation (r = +0.82) between MAR and virulence of bacteria in polluted aquatic ecosystems, and highlight the potential of drains as reactors for their amplification and dissemination. The study suggests regular monitoring for antibiotics resistance in native bacteria of River Nile, prohibition of unregulated use of antibiotics, and proper management for wastes disposal.